The egalitarian moment Asia and Africa, 1950-1980 - Low, D. A (Cambridge Cambridge University Press, 1996)
This book outlines a major feature of twentieth-century world history that arguably affected more people than the rise and fall of Soviet Communism. It is the first to discuss as related developments the many attempts in Asia and Africa in the third quarter of the twentieth century to create egalitarian rural societies (landlord abolition in Egypt, India and Iran; ujamaa in Tanzania; land reform in Indonesia; collectivization in China, Vietnam and Ethiopia), their failure, and the differentiated rural regimes that despite landlord abolition remain there to this day.
Includes bibliographical references and index.
Keywords: Equality--Asia--History--20th century